Unveiling the therapeutic potential of HZQYF: exploring the inhibitory impact of a clinical herbal formula on gastric cancer through network pharmacology and transcript analysis - Zhong Feng; Ling Ou; Hui Li; Yajie Hao; Ruixia Wei; Guimin Zhang; Meicun Yao (BMC Complementary Medicine and Therapies)
Abstract Hezi Qingyou Formula (HZQYF) is a clinical formulation known for its efficacy in treating gastrointestinal diseases. Nevertheless, its specific impact and underlying mechanism of action in gastric cancer remain to be fully elucidated. The major components of the formula were precisely identified and characterized using ultra-high-performance liquid chromatography coupled with a tandem mass spectrometer (UHPLC-MS/MS). Network pharmacology and transcript analysis were utilized to identify the targets associated with drug-disease interactions. Subsequently, Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), and Reactome analyses were conducted to unravel the pivotal pathways involved. Furthermore, in vitro experiments were performed to validate the anti-gastric cancer activity of HZQYF, including assessments of cell viability and clonogenic potential. These results revealed that 260 co-expressed targets were identified as shared between HZQYF and gastric cancer. These genes were significantly enriched in biological processes and pathways related to steroid metabolism, gamma-aminobutyric acid (GABA)-A receptor complex, steroid binding activity, extracellular ligand-gated ion channel activity, chemical carcinogenesis-reactive oxygen species, and GABAergic synapse. Furthermore, the principal components of the formula were characterized. Subsequent cell experiments confirmed the formula's ability to inhibit gastric cancer activity and suppress colony formation in vitro. In conclusion, these findings suggest that Hezi Qingyou Formula may exert its anti-gastric cancer activity by influencing reactive oxygen species and modulating GABAergic synapses in-silico methods. This study provides a foundation for further exploration of HZQYF as a potential therapeutic agent for gastric cancer.